Malignant Peripheral Nerve Sheath Tumor in the Maxilla: Report of a Rare Case - Jahanshah Salehinejad; Atefeh Nasseh; Amir Hossein Jafarian; Nazanin Bashardoust (Mashhad University of Medical Sciences, 2013)
Malignant peripheral nerve sheath tumor (MPNST) is a rare malignant tumor that develops either from a preexisting neurofibroma or de novo. The cell of origin is believed to be the Schwann cell and possibly other nerve sheath cells. In this report, we describe a rare case of MPNST that arise from the socket of second left maxillary molar that has been already extracted in a young man. He was referred to a dentist's office with a tumor-like mass of soft tissue on his left maxillary gingiva. Biopsy and histopathologic examination was performed and based on histologic and immuno-histochemical findings, the diagnosis of MPNST was made. MPNST is a rare malignant tumor in the oral cavity. Dentists must be careful and conscious because this rare malignancy can occur in gingiva and can mimic the clinical feature of any benign gingival enlargements.